2019
DOI: 10.1111/bjet.12740
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality‐based virtual manipulatives versus physical manipulatives for teaching geometric shapes to preschool children

Abstract: The aim of the current study is to compare the effect of virtual and physical manipulatives on preschool children’s understanding of geometric shapes. A quasi‐experimental research design was employed where children in the experimental group used tablet computers to access Augmented Reality (AR)‐based virtual manipulatives, while children in the control group used physical manipulatives. The instruction lasted for a period of four weeks at a public primary school in Turkey with 72 children aged five and six ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…This finding is in accordance with previous studies (e.g. [8] [16]) showing that there are high levels of motivation among young children when they are first exposed to AR technology.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in accordance with previous studies (e.g. [8] [16]) showing that there are high levels of motivation among young children when they are first exposed to AR technology.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, recent studies have explored AR and its influence on mathematics education in early childhood, including the learning of subitizing and equipartitioning [15] and geometry [16]. The main purpose of these studies was to examine whether it was possible to improve the relative mathematical skills of children through the use of AR technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the use of multimedia can affect spatial abilities (Heo & Toomey, 2019). Some of the media that are often used in learning geometry are tangram (Bergstrom & Zhang, 2016;Moursund, 2007), geoboard (Mudaly & Sibiya, 2018;Trimurtini, Safitri, Sari, & Nugraheni, 2020), android-based media (Bektiningsih, Nugraheni, & Sari, 2020), geogebra (Başara, 2020;Klemer & Rapoport, 2020;Topuz & Birgin, 2020) electronic module (Suastika & Wahyuningtyas, 2020), augmented (İbili, Çat, Resnyansky, Şahin, & Billinghurst, 2019) and virtual reality-based media (Gecu-parmaksiz & Delialioglu, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have indicated that AR promotes enhanced learning (Abbasi, Waseem, & Ashraf, 2017;Akçayır & € Okçe Akçayır, 2017;Amaia, Inigo, Jorge, & Enara, 2016;Billinghurst & Duenser, 2012;Bratitsis, Bardanika, & Ioannou, 2017;Chen, Ho, & Lin, 2015;Li, van der Spek, Hu, & Feijs, 2017;Martinez, Benito, Gonzalez, & Ajuria, 2017;Umer, Nasir, Khan, Ali, & Ahmed, 2017), many educational AR applications suffer from usability issues, especially when their design does not account for the physical and cognitive skills of the target age group (Radu, MacIntyre, & Lourenco, 2016). Researchers have explored educational AR applications to help children learn mathematics and science literacy (Dunleavy, Dede, & Mitchell, 2009), teaching geometric shapes to preschool children (Gecu-Parmaksiz & Delialioglu, 2019), and even to support young students with autism spectrum disorder (ASD) (Lumbreras & Ariel, 2018) and Dyscalculia (Avila-Pesantes et al, 2018). Common challenges include physical, cognitive, and socio-emotional development, motor abilities, spatial cognition, attention, logic and memory, and other disability issues (Radu & MacIntyre, 2012;Lin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%